Archaeal community from the Northern Hangzhou Bay to the East China Sea: biogeography, ecological processes, and functional potential - Tian, Cunzhang; He, Xinping; Zhou, Hongwei; Liu, Cheng; Gao, Dengzhou; Chang, Yongkai; Zhao, Shanshan; Zhang, Wensong; Zhang, Zongxiao (Frontiers in Marine Science, 2024)
Introduction Archaeal communities play a crucial role in marine ecosystems, yet our understanding of their ecological and functional traits remains incomplete. This study focuses on northern Hangzhou Bay to fill gaps in knowledge regarding the biogeography and functionality of archaeal groups. Methods We utilized a high-throughput sequencing dataset based on the 16S rRNA gene to characterize the archaeal community, aiming to identify biogeographic patterns and assess the influence of environmental factors on community structure. Results The predominant phyla identified were Woesearchaeota, Thaumarchaeota, Euryarchaeota, and Crenarchaeota. Archaeal community structure in sediments showed a geographical pattern along the environmental gradient, influenced by factors such as salinity, ammonium, total phosphorus, pH, and total nitrogen content. Network analysis revealed nonrandom co-occurrence patterns, with associations changing along the salinity gradient. Additionally, this study directly proved the existence of dispersal limitation in this strongly connected marine ecological system through null model analyses. Variation in the archaeal community was attributed to both environmental constraints and stochastic processes due to dispersal limitation. Furthermore, our results revealed that the key biogeochemical functions of the archaeal community also exhibited a clear salinity gradient, the functional differences appear to be influenced by salinity, and the critical roles of archaeal diversity were highlighted. Discussion All these findings enhance our understanding of microbial ecology and element transformation in estuarine environments. The highlighted roles of archaeal diversity and the influence of environmental factors on community structure and function underscore the complexity of marine microbial ecosystems.